SEM AND STM INVESTIGATIONS OF NANOWIRES - G. Sh. Shmavonyan
Vapor-phase epitaxy grown ZnO nanowires on a Si substrate have been investigated by SEM and STM. The sizes of nanowires were determined.
Keywords: Physics; Electronic structure and electrical properties of surfaces